Kepemimpinan Kiai dalam Mengembangkan Pendidikan Pesantren - Ahmad Faris (Institut Ilmu Keislaman Annuqayah, 2015)
Pesantren as an educational institution has its own characteristics, so that schools can be distinguished from other educational institutions. Characteristic of schools considered to be very unique by the observer of education, from tradition, curriculum, education system, infrastructure, kiai leadership models, and also the lifestyle of the students were very simple and put together. So that attract many researchers to continue research and study of the pesantren. Management of pesantren education can not be separated from the role of kiai. Kiai has a major role that determines the course of the management of all schools. At the pesantren kyiai is a figure who occupied as the highest structrue in the management of the school. Kiai which controls and determines everything in pesantren. Kiai has demonstrated success in managing the schools, from the first starting early embryo until now in the face of development. It can be seen from the rapid increase in the number of students from year to year and owned infrastructure continues to increase and the quality of students in terms of their knowledge is not inferior to the products of non pesantren education institutions.